2003
DOI: 10.2307/4003936
|View full text |Cite
|
Sign up to set email alerts
|

Big Sacaton and Endophyte-Infected Arizona Fescue Germination under Water Stress

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Allen Press and Society for Range Management are collaborating with JSTOR to digitize, preserve and extend access to Journal of Range Management. AbstractWater availability in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…The lower germination of seeds under natural conditions compared to that in the laboratory indicates that the sub-arctic winter constrains seedling establishment and thus growth rate of F. rubra populations by reducing seed germination. Similarly to some past studies focusing on natural grass populations (Faeth 2002;Neil et al 2003;Hamilton and Faeth 2005), no diVerences in germination success between endophyte-infected and endophyte-free seeds of F. rubra and F. ovina were detected in the greenhouse experiment. However, endophyte-free red fescue seeds from river banks had higher germination incidence after the winter exposure than endophyte-infected seeds Table 2 EVects of treatments and a covariate (seedling number/pot) on the performance of red fescue (Festuca rubra s.l.)…”
Section: Discussionsupporting
confidence: 44%
“…The lower germination of seeds under natural conditions compared to that in the laboratory indicates that the sub-arctic winter constrains seedling establishment and thus growth rate of F. rubra populations by reducing seed germination. Similarly to some past studies focusing on natural grass populations (Faeth 2002;Neil et al 2003;Hamilton and Faeth 2005), no diVerences in germination success between endophyte-infected and endophyte-free seeds of F. rubra and F. ovina were detected in the greenhouse experiment. However, endophyte-free red fescue seeds from river banks had higher germination incidence after the winter exposure than endophyte-infected seeds Table 2 EVects of treatments and a covariate (seedling number/pot) on the performance of red fescue (Festuca rubra s.l.)…”
Section: Discussionsupporting
confidence: 44%
“…It has been found that endophyte infection increases germination in Festuca arundinacea (Pinkerton et al 1990), Lolium perenne (Clay 1987) and Bromus setifolius (Novas et al 2003), and there are also reports about the effect of Neotyphodium on the germination of DHG (Li 2005(Li , 2007Gou 2007). However, some studies have reported that an endophyte does not affect seed germination of Festuca arizonica (Neil et al 2003;Faeth et al 2004) or Festuca arundinacea (Bacon 1993). It can be argued that these inconsistencies arise from comparing experiments in which endophyte effects were confounded by the genetic origin of the host plants, and also with the conditions of seed production and afterripening (Gutterman 2000;Pedro et al 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Several studies revealed that seeds of some arid plant species have an adaptation to germinate under water stress at water potentials as low as À1.0 MPa (Schütz et al 2002) andeven À1.5 MPa (Evans andEtherington 1990;Briedé and McKell 1992;Neil et al 2003), and that desert plants have faster germination than plants living in wetter areas (Jurado and Westoby 1992). Accordingly, the ability to germinate fast and at low water potentials are advantages that may be vital for species colonising arid and semiarid environments (Evans and Etherington 1990).…”
Section: Introductionmentioning
confidence: 97%